Experimental and theoretical study on extraction and recovery of naphthenic acid using dicyanamide-based ionic liquids - Ismail, M. (2019)
Naphthenic acid is a toxic component that is present in the crude oil. It causes severe operational problems for oil refineries. However, naphthenic acid is a useful raw material for many industrial processes. Thus, it is advantageous to extract and recover the naphthenic acid from crude oil. Ionic liquid has been considered as an environmental friendly material that can be used to extract naphthenic acid from crude oil. However, the characteristics of the ionic liquids to achieve the best extraction efficiency is still not completely known. In this research, the performance of the ionic liquids consists of diazabicyclo undecene (DBU) based cations and dicyanamide (DCN) anion in the extraction of naphthenic acid from acidic model oil was studied. Computer simulation of a mixture of naphthenic acid, ionic liquid, and n-dodecane was also performed. The study showed that the DBU-DCN based ionic liquids can effectively extract naphthenic acid from highly acidic model oil. The increase in the alkyl chain length on the cation increases the percent naphthenic acid extraction. Molecular simulation studies showed that the dicynamide anion interacting directly with the naphthenic acid. The alkyl chain on the DBU cation does not form any cage around the naphthenic acid as previously proposed. The study suggests that the biggest factor affecting naphthenic acid extraction efficiency is the extent of solubility of the polar ionic liquid in the non-polar oil. Â© 2018 Elsevier B.V.